When numbers make you feel : impact of round versus precise numbers on preventive health behaviors - Wadhwa, Monica (2020)
Six experiments found that people are more likely to engage in preventive behaviors when they are exposed to preventive messages, which present health-related numerical cues as round numbers (e.g., 15.00%) versus precise numbers (e.g., 15.29%). When participants were exposed to round numbers in preventive messages, they indicated a higher intention to get vaccinated against flu, spent longer time flossing their teeth and were more likely to reduce their consumption of unhealthy food, compared with when they were exposed to precise numbers. Providing evidence for an affect-based mechanism, the current research shows that round numbers intensify people’s negative affective reactions toward the health risk, which, in turn, increase their likelihood to engage in preventive behaviors. These findings indicate that presenting health-related numerical cues as round versus precise numbers in preventive messages can have a powerful impact on preventive behaviors.